2014
DOI: 10.1684/ejd.2014.2399
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and severity of skin and nail involvement in patients with plaque psoriasis

Abstract: A. Various colour gradations as a dermatoscopic feature of cutaneous angiosarcoma of the scalp. Australas J Dermatol 2013; 54: 36-8. 2. Cuperus E, Leguit R, Albregts M, Toonstra J. Post radiation skin tumors: basal cell carcinomas, squamous cell carcinomas and angiosarcomas. A review of this late effect of radiotherapy. Eur J Dermatol 2013; 23: 749-57. 3. Ulbright TM, Clark SA, Einhorn LH. Angiosarcoma associated with germ cell tumors. Hum Pathol 1985; 16: 268-72. 4. Kim MK, Huh SJ, Kim DY, et al. Secondary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Hallaji et al [24] reported significant correlation between total NAPSI and PASI in patients with plaque psoriasis. Van der Velden et al [16] reported no significant correlation between NAPSI and PASI, whereas Kyriakou et al [25] reported significant correlation (r = 0.515; p = 0.029). Wanniang et al [14] reported significant positive correlation between PASI and dermoscopic NAPSI scores (r = 0.34; p = 0.013).…”
Section: Discussionmentioning
confidence: 99%
“…Hallaji et al [24] reported significant correlation between total NAPSI and PASI in patients with plaque psoriasis. Van der Velden et al [16] reported no significant correlation between NAPSI and PASI, whereas Kyriakou et al [25] reported significant correlation (r = 0.515; p = 0.029). Wanniang et al [14] reported significant positive correlation between PASI and dermoscopic NAPSI scores (r = 0.34; p = 0.013).…”
Section: Discussionmentioning
confidence: 99%
“…Across studies, psoriasis with nail involvement was associated with significantly higher baseline PASI scores [9][10][11][12][13][14][15]. Nail involvement was also associated with significantly greater QoL impairment [9][10][11][12][13][14][15]. In studies with subgroup analysis by gender, women had higher PASI and DLQI scores than men [10,12,13].…”
Section: Psoriasis Severity and Quality Of Lifementioning
confidence: 95%
“…The mean age of subjects across studies was between 43.3 and 57.5 years [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Composition of females in study samples also varied from 19.2 to 63.0% [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The mean duration of psoriasis in those with nail involvement ranged from 11.5 to 34.3 years [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations